Peningkatan Daya Saing Keripik Melalui Perajang Slice Kentang dan Desain Kemasan di Sumberejo, Ngablak, Magelang - Choiroel Anam; Rhina Uchyani; Emi Widiyanti (PRIMA: Journal of Community Empowering and Services, 2020)
Title: Improved Chips Competitiveness Through Potato Slice Chopper and Packaging Design in Sumberejo, Ngablak, MagelangPotato post-harvest handling in the Merbabu agropolitan area of Sumberejo Village, Magelang Regency was needed in order to optimize both quantity and quality, so both producers and consumers were benefit. Abundant potato production was potentially being processed into potato chips and become an icon of tourist souvenirs on the Merbabu mountain slopes. The introduction of this Appropriate Technology is an effort to increase the competitiveness of processed potato products in the Merbabu slope area with various activities such as facilitation of potato chip production equipment, introduction of potato stick and slice machines, potato processing training for SMEs, improvement of packaging design, management of business legality in the form of P-IRT, and facilitation of the balance. The results of this activity were able to increase the production capacity of potato chips 17-20% per month, to increase the quality of potato chips which is more uniform and to extend product shelflife. Product diversification was produced by processing potatoes into "Merbabu Potato Donuts" and "Merbabu Potato Cake". Overall increasing in sales turnover of processed potato products and increasing product competitiveness could increase the income of the Agro Lestari Merbabu potato farmers group.